2004
DOI: 10.1074/jbc.m400149200
|View full text |Cite
|
Sign up to set email alerts
|

Role of the N-terminal Catalytic Domain of Angiotensin-converting Enzyme Investigated by Targeted Inactivation in Mice

Abstract: Angiotensin-converting enzyme (ACE) produces the vasoconstrictor angiotensin II. The ACE protein is composed of two homologous domains, each binding zinc and each independently catalytic. To assess the physiologic significance of the two ACE catalytic domains, we used gene targeting in mice to introduce two point mutations (H395K and H399K) that selectively inactivated the ACE N-terminal catalytic site. This modification does not affect C-terminal enzymatic activity or ACE protein expression. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 35 publications
4
91
0
1
Order By: Relevance
“…As previously reported, we found that ACE was highly expressed in kidney and lung but absent in the liver (36). In the brain, we observed similar expression of ACE protein in the cerebral cortex, hippocampus, cerebellum, and basal ganglia/brainstem (Fig.…”
Section: Expression and Characterization Of Transfected Human Ace-tosupporting
confidence: 73%
“…As previously reported, we found that ACE was highly expressed in kidney and lung but absent in the liver (36). In the brain, we observed similar expression of ACE protein in the cerebral cortex, hippocampus, cerebellum, and basal ganglia/brainstem (Fig.…”
Section: Expression and Characterization Of Transfected Human Ace-tosupporting
confidence: 73%
“…1, C and F), suggesting that each catalytic domain of ACE regulates the activity of the other, and both domains are required for normal substrate recognition and degradation. Mice with a selective inactivation of either the N-or C-domain of ACE were generated, and the C-domain was demonstrated to be the main site of angiotensin I cleavage (18,22), which is consistent with our in vitro finding. However, the role of the N-domain of ACE toward A␤42 to A␤40 conversion in vivo needs to be addressed.…”
Section: Discussionsupporting
confidence: 78%
“…26,27 We, therefore, asked whether MWF rats could exhibit changes in antifibrotic Ac-SDKP levels that may reflect altered Prep-dependent generation and/or ACE-mediated clearance of the peptide, and also, we asked whether they could be modulated as part of the renoprotective action of ACEi.…”
Section: Modulation Of Ac-sdkp Contributes To Reduction Of Interstitimentioning
confidence: 99%